Study of the effect of adding marine sand with bentonite on bentonite properties Egyptian. - خضور علي; فياض توفيق; العبده رامي (Latakia University Journal -Engineering Sciences Series, 2023)
piles are used as deep foundations for high- rise building structure, the pile transfer the applied loads to the soil by lateral friction of the piles with the soil and the anchorage at the end of the pile foot. During excavation of borehole, bentonite is used to support the wall of the borehole and to avoid soil collapse in the borehole, due to its high swelling property. When the piles are poured the bentonite rises due to the lower density and the concrete settles at the bottom of the hole. A viscous and weakly frictionless layer with a of (filter cake) around the pile body, which causes a decrease in the friction bearing capacity of the piles, because of viscosity of bentonite. This study includes study the effect of adding Marine sand to bentonite rates different on properties bentonite Egyptian (Atterberg limits –Volumetric weight – Specific weight – Shear– Odometric modulus of elasticity –Viscosity – Degree of swelling), by conducting a number of laboratory experiments on bentonite treated with sand at each addition ratio and approving the average results, to obtain the best addition ratio of marine sand, improve the shear properties and modulus of elasticity of bentonite and maintain the workability of Egyptian bentonite.